2013
DOI: 10.1039/c3fo60075k
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy and composition of raw acorn starch in relation to in vivo starch digestibility

Abstract: The structure and composition of starch play an important role as co-factors affecting raw starch digestibility: such features were investigated in raw acorn starch from the most diffused oak trees in the Mediterranean basin. A total of 620 whole ripe acorns from Holm (Quercus ilex L., n = 198), Downy (Quercus pubescens Willd., n = 207) and Cork (Quercus suber L., n = 215) oaks sampled on the Sardinia Isle (40° 56' 0'' N; 9° 4' 0'' E; 545 m above the mean sea level) in the same geographical area, were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…The amylose content of wild mango starch (25.5 ± 0.2% w/w dwb of starch) was not significantly different from that of maize starch (24.4 ± 1.0% w/w dwb), but was significantly ( p ≤ 0.05) lower than that of bean (30.9 ± 1.3% w/w dwb) and pea (31.7 ± 0.5% w/w dwb) starches. The amylose content of the wild mango seed starch was within the range (19.5–34.0%) reported for acorn starch . The amylose contents of bean, pea, and maize starches reported in the present study were consistent with those reported in the literature for maize, pea, and bean starches .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The amylose content of wild mango starch (25.5 ± 0.2% w/w dwb of starch) was not significantly different from that of maize starch (24.4 ± 1.0% w/w dwb), but was significantly ( p ≤ 0.05) lower than that of bean (30.9 ± 1.3% w/w dwb) and pea (31.7 ± 0.5% w/w dwb) starches. The amylose content of the wild mango seed starch was within the range (19.5–34.0%) reported for acorn starch . The amylose contents of bean, pea, and maize starches reported in the present study were consistent with those reported in the literature for maize, pea, and bean starches .…”
Section: Resultssupporting
confidence: 91%
“…The wild mango starch granules were also smaller than similarly shaped granules reported in literature, such as cassava (15 µm), jackfruit (7.6 µm), tannia (14.7 µm), and sago (30 µm) starch granules. The wild mango seed starch granules were also smaller than those reported for acorn starch (10.2–43.3 μm) . The wild mango starch granule size showed a normal/unimodal distribution with a narrower distribution than bean, pea, and maize starches (Figure ).…”
Section: Resultsmentioning
confidence: 71%
“…Paste retrogradation is influenced by the amylose content and also by the structural arrangement of the starch chains [37,38]. According to Hager et al [35], buckwheat starch presents a granular shape, whereas acorn starch granules show a spheroid/ovoid and cylindrical shape [43].…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Since our study is focused on acorn flour, it is important to highlight that among the different species of oak trees, the acorn starch is also different due to taxonomic characteristics of the plant [43]. For this reason, to make possible the comparison about starch behaviour, we used the studies based on the same species: Quercus rotundifolia and Quercus ilex from Cappai et al [43] and Correia et al [39].…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Nutrient composition of acorns identifies these fruits as energy-rich feedstuffs (starch 512–571 g and 42–63 g crude fat content in kg dry matter) [ 14 ]. Therefore, acorns can serve as concentrate feeds in extensive breeding systems [ 14 ] chiefly in feed mixtures [ 15 , 16 ] due to biologically active compounds (polyphenols profile) and to the peculiar pattern of fatty acids [ 14 ]. A number of studies on the use of acorns was carried out in pigs and, to a lesser extent, in ruminants and poultry.…”
Section: Introductionmentioning
confidence: 99%